Parelaphostrongylus tenuis Cerebrospinal Nematodiasis in a Horse with Cervical Scoliosis and Meningomyelitis. (20th March 2017) - Mittelman, N.S.; Divers, T.J.; Engiles, J.B.; Gerhold, R.; Ness, S.; Scrivani, P.V.; Southard, T.; Johnson, A.L.
Abstract : There are reports of horses with acute onset acquired cervical scoliosis and cutaneous analgesia. The underlying dorsal gray column myelitis that produces these neurologic signs has been only presumptively attributed to migration of Parelaphostrongylus tenuis within the spinal cord. Despite previous confirmation brain by polymerase chain reaction testing, of P. tenuis within the brain of horses by polymerase chain reaction testing, genetic testing has failed to definitively identify the presence of this parasite in cases of equine myelitis. This case report provides molecular confirmation via polymerase chain reaction of P. tenuis within the cervical spinal cord of a horse with scoliosis and cutaneous analgesia.